Suicide etiology in youth: Differences and similarities by sexual and gender minority status. (July 2019) - McKay, Tasseli; Berzofsky, Marcus; Landwehr, Justin; Hsieh, Patrick; Smith, Amanda
Abstract: Sexual and gender minority (SGM) individuals are at steeply elevated risk for suicide, particularly in adolescence and young adulthood. Evidence on suicide risk factors specific to SGM youth is emerging, but an integrated understanding of the etiology of suicide that accounts for both commonalities and differences between SGM and non-SMG youth is lacking. Using 2018 data from a social media-based sample of SGM (n = 175) and non-SGM (n = 310) youth ages 14–21, we assess the role of constructs from the general-population-based interpersonal-psychological theory of suicide and the SGM-specific minority stress theory in suicide ideation and attempt. Parental support was a strong protective factor shared across the SGM and non-SGM youth samples. The role of other factors, such as racial/ethnic identity, differed by group. Implications for suicide prevention and intervention in schools and other settings that include both SGM- and non-SGM youth are discussed. Highlights: Sexual and gender minority youth were more than twice as likely to be suicidal. Feeling that parents cared was strongly protective against suicidality. Online and school-based bullying and safety-related truancy put youth at risk.